Illiquidity Exposure of Size and Value in Malaysian Equity Returns - Mohamad, Jais; Chandana, Gunathilaka (The IBFR, 2016)
This study examines pricing implications of size,value,illiquidity and momentum effects in Malaysia stock returns. It employs time series and panel methods in testing APT-motivated pricing models over a sample period of 14 years up to 2013. Results indicate the significance of illiquidity over size and value factors. Capital Asstes Pricing Model (CAPM) poorly performs in explaining average stock return. An asset's exposure to size,value,momentum and illiquidity characteristics subordinates CAPM's explanatory power. Momentum trading strategy is profitable in short to intermediate horizons, yet momentum risk factor is unable to improve the efficiency of pricing models. Application of illiquidity adjusted Fama-French three-factor model is apparently persuasive for investments and related decisions in Malaysia.